Factors that interfere with total physical inactivity in overweight women - Fernanda Carneiro Mussi; Taise Santos do Nascimento; Cátia Suely Palmeira; Francisco José Gondim Pitanga; Flávia Silva Ferreira; Ana Carla Carvalho Coelho; Carlos Antônio de Souza Teles Santos (Universidade Federal do Ceará, 2021)
Objective: to investigate the variables that interfere with total physical inactivity in overweight women. Methods: cross-sectional research that collected sociodemographic data, self-perceived health, self-efficacy for physical activity, weight, and height in 142 women. The International Physical Activity Questionnaire was used to evaluate physical activity. Descriptive and inferential statistics were used. A 5% statistical significance level was adopted. Results: the prevalence of total physical inactivity was 34.5%. A significant association between total physical inactivity and age was found in the bivariate analysis. In the multivariate analysis, only women with regular and poor self-perceived health showed an increase of 124% and 150%, respectively, of total physical inactivity. Conclusion: physical inactivity was associated with regular and poor self-perception of health, being a health parameter for the development of health promotion policies and actions.